2008
DOI: 10.4141/cjss08012
|View full text |Cite
|
Sign up to set email alerts
|

Model prediction of soil drainage classes based on digital elevation model parameters and soil attributes from coarse resolution soil maps

Abstract: Model prediction of soil drainage classes based on digital elevation model parameters and soil attributes from coarse resolution soil maps. Can. J. Soil Sci. 88: 787Á799. High-resolution soil drainage maps are important for crop production planning, forest management, and environmental assessment. Existing soil classification maps tend to only have information about the dominant soil drainage conditions and they are inadequate for precision forestry and agriculture planning purposes. The objective of this rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…The lack of an independent dataset to validate Rs models is typical of similar studies [ Bond‐Lamberty and Thomson , ; Chen et al ., , ; Hashimoto et al ., ; Li et al ., ]. For this study, according to methods that have been accepted in the ANN modeling community [ Zhao et al ., ; Wen et al ., ], one dataset (including one of candidate inputs and corresponding Rs field records) was first divided into a calibration dataset (80% of the total) and a validation dataset (20% of the total). The calibration dataset was used to build the ANN model, and the validation dataset was used to examine the performance of the ANN model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of an independent dataset to validate Rs models is typical of similar studies [ Bond‐Lamberty and Thomson , ; Chen et al ., , ; Hashimoto et al ., ; Li et al ., ]. For this study, according to methods that have been accepted in the ANN modeling community [ Zhao et al ., ; Wen et al ., ], one dataset (including one of candidate inputs and corresponding Rs field records) was first divided into a calibration dataset (80% of the total) and a validation dataset (20% of the total). The calibration dataset was used to build the ANN model, and the validation dataset was used to examine the performance of the ANN model.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of an independent dataset to validate Rs models is typical of similar studies [Bond-Lamberty and Thomson, 2010;Chen et al, 2010Chen et al, , 2013Hashimoto et al, 2015;Li et al, 2017]. For this study, according to methods that have been accepted in the ANN modeling community [Zhao et al, 2008;Wen et al, 2014], one dataset (including one ANN, artificial neural network; MAT, mean annual temperature; MAP, mean annual precipitation; SOC, soil organic carbon; LAI, leaf area index; NPP, net primary production. a Correlation coefficients between the field-measured annual Rs and predicted annual Rs using an linear model that used a single predictor as input.…”
Section: Artificial Neural Network Modelmentioning
confidence: 99%
“…This is based on the possibility that the original land cover types (forest) before settlement had impacts on soil formation for a long time compared with current land uses, which may have had relatively less time to affect soil formation. The SDR map was generated with the Spatial Analyst Extension of ArcGIS (ESRI 1999Á2005;Zhao et al 2008). …”
Section: Variables Derived From Digital Elevation Modelmentioning
confidence: 99%
“…A number of researchers have shown that the ANN model can be used to establish relationships through linear or non-linear functions (Levine et al 1996;Levine and Kimes 1997;McBratney et al 2000;Licznar and Nearing 2003;Zhao et al 2008). In this study, we developed an ANN model to predict SOC content based on soil attributes extracted from widely available coarse resolution maps (1:1 000 000 scale) and digital elevation model (DEM) derived parameters (1:35 000 scale).…”
mentioning
confidence: 99%
“…The climate of the region is considered to be moderately cool boreal with approximately 120 frost-free days [2]. The average temperature is 3.7 • C and annual precipitation is 1037.4 mm [21,25,26]. About one-third of the precipitation is in the form of snow.…”
Section: Study Areamentioning
confidence: 99%